Afro-Latin@s in Movement
XVII, 316 p. 9 illus., 4 illus. in color.
Keywords: This book considers how ideas about blackness travel across the Americas via migration, and media, cultural, and political exchanges. It examines African-descended populations in Latin America and Afro-Latin@s in the United States in order to explore questions of black identity and representation, transnationalism, and diaspora. Afro-Latin@s in Movement explores diverse topics—from popular music to sports to political organizing—to consider the ways that blackness is imagined, embodied, and understood across the Americas. .